Fishing - Schwipps, Greg; Kaminsky, Peter (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
Millions of folks find fishing relaxing, challenging, entertaining... and a great way to spice up dinner. This 3rd edition of the guidebook shows you everything you need to know about the necessary gear, where different kinds of fish hang out, what types of bait and lures to stock, how to stay safe on the water, and even how to clean and cook your catch. Plus, you'll learn about the latest high-tech fishing gadgets and GPS hacks, get advice on fishing from boats, and much more. Here's where to drop your line!
Includes index.
Keywords: Fishing; Fishing -- Technique; Cooking (Fish)